Enhancing Students' Visual-Spatial Abilities through the Use of Bonat Berakal Media in Understanding Shapes of Molecules - Anggun Winata (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Students in 10th grade often get low learning outcomes on one of the chemical concepts, the shapes of molecules. Based on the test results, it can be seen that most students have difficulty on understanding and drawing the shapes of molecules. Many students have difficulty drawing shapes of molecules because shapes of molecules cannot be observed directly using the sense of sight, so students cannot project molecular images on their minds. The inability of students to understand molecular drawings in predicting the shape of molecules may be related to spatial visual abilities. The study aimed to investigate the effectiveness of using Bonat berakal media in enhancing tenth-grade students' visual-spatial abilities in understanding shapes of molecules. The students from classes A, B, and C in academic year 2022/2023 at SMAN 1 Tuban participated in the study. The research design was one group pre-test post-test. The instruments used were a teaching module on shapes of molecules and a spatial visual test. The data was analyzed using N-Gain score. The results showed that the pre-test average of students' spatial visual abilities was low but improved to a high category post-test. The study concluded that the use of Bonat berakal media was effective in improving students' visual-spatial abilities in shapes of melecules concepts, as indicated by an N-Gain score of 0.620.